Public support for older disabled people: Evidence from the English Longitudinal Study of Ageing on receipt of disability benefits and social care subsidy - Ruth Hancock; Marcello Morciano; Stephen E. Pudney (University of East Anglia, Health Economics Group (HEG), 2016)
In England, state support for older people with disabilities consists of a national system of non-means tested cash disability benefits, and a locally-administered means-tested system of social care. Evidence on how the combination of the two systems targets those in most need is lacking. We estimate a latent factor structural equation model of disability and receipt of one or both forms of support. The model integrates the measurement of disability and its influence on receipt of state support, allowing for the socio-economic gradient in disability, and adopts income and wealth constructs appropriate to each part of the model. We find that receipt of each form of support rises as disability increases, with a strong concentration on the most disabled, especially for LA-funded care. The overlap between the two programmes is confined to the most disabled. Less than half of recipients of local authority-funded care also receive a disability benefit; a third of those in the top 10% of the disability distribution receive neither form of support. Despite being non means-tested, disability benefits display a degree of income and wealth targeting, as a consequence of the socio-economic gradient in disability and likely disability benefit claims behaviour.
Keywords: H24; I18; I38; C30; 330; older people; disability; social care; disability benefits; target efficiency; English Longitudinal Study of Ageing (ELSA)